2021
DOI: 10.1371/journal.pone.0255541
|View full text |Cite
|
Sign up to set email alerts
|

Examining the potential benefits of the influenza vaccine against SARS-CoV-2: A retrospective cohort analysis of 74,754 patients

Abstract: Introduction Recently, several single center studies have suggested a protective effect of the influenza vaccine against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). This study utilizes a continuously updated Electronic Medical Record (EMR) network to assess the possible benefits of influenza vaccination mitigating critical adverse outcomes in SARS-CoV-2 positive patients from 56 healthcare organizations (HCOs). Methods The de-identified records of 73,346,583 patients were retrospectively sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 28 publications
5
46
0
3
Order By: Relevance
“…At 30, 60, 90, and 120 days of SARS-CoV-2-positive diagnosis, patients in the cohort that received the influenza vaccine showed a significantly reduced risk for all outcomes. The authors of the study suggest that influenza vaccination may exert a potential protective effect that could benefit populations without ready access to COVID-19 vaccination [36]. In the present study, none of the patients in the COVID-19 group received a diagnosis of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…At 30, 60, 90, and 120 days of SARS-CoV-2-positive diagnosis, patients in the cohort that received the influenza vaccine showed a significantly reduced risk for all outcomes. The authors of the study suggest that influenza vaccination may exert a potential protective effect that could benefit populations without ready access to COVID-19 vaccination [36]. In the present study, none of the patients in the COVID-19 group received a diagnosis of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 50%
“…This mechanism has been demonstrated in the protective effect of BCG vaccination of human malaria infection [35]. The potential benefit of influenza vaccination mitigating critical outcomes in patients with SARS-CoV-2 infection, such as sepsis, stroke, deep vein thrombosis, and emergency and ICU admissions, was analyzed in a retrospective analysis of two cohorts of 37,377 patients, having either received or not received influenza vaccination between 6 months and 2 weeks prior to COVID-19 infection [36]. Data were analyzed using a strict propensity score matching procedure adjusted by age, race, gender, ethnicity, hypertension, hyperlipidemia, diabetes, obesity, heart disease, chronic obstructive pulmonary disease, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against SARS‐CoV‐2 as well as against recognized coinfections such as Streptococci, Haemophilus , and influenza virus should decrease risk of coagulopathies by preventing bystander or complementary co‐infections, just as they decrease risk of severe COVID‐19 in general. [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ] Additionally, the results reported here may provide insight into the causes of menstruation alterations reported by some women following SARS‐CoV‐2 vaccination. [ 112 ] Finally, the present work has implications for future SARS‐CoV‐2 vaccine design, implying that whole virus SARS‐CoV‐2 vaccines may present an extraordinary risk of inducing coagulopathies compared with the mRNA, peptide, or subunit vaccines because of the very large number of blood protein mimics present; however removing molecular mimicry regions from SARS‐CoV‐2 mRNAs, proteins and their virus vectors may significantly improve vaccine safety.…”
Section: Conclusion: Testing and Preventing Covid‐19 Autoimmunity And Making Vaccines Safermentioning
confidence: 83%
“…However, more studies are needed to comprehensively evaluate cost-effectiveness. Finally, a recent study of two cohorts of 37,377 patients with SARS-CoV-2 infection found that influenza-vaccinated patients had significantly less often sepsis, stroke, deep vein thrombosis, emergency department and intensive care unit admissions which indicate a potential protective effect against SARS-CoV-2 [ 30 ]. Further investigation is needed.…”
Section: Knowledge and Attitudes Of Hcp Towards Influenza And Influenza Vaccinationmentioning
confidence: 99%